David Campbell performing on stage in 1975 - Mariposa Folk Foundation (1975)
Title based on content of image. Image of David Campbell performing on the Native Peoples Area Stage. Annotations on slide include: "KB. N.P. David Campbell" Slide stamp 31. Digitization possible through funding from Young Canada Works grant for the summer of 2018. We acknowledge the financial support of the Government of Canada. Nous reconnaissons l'appui financier du gouvernement du Canada.